Legal Certainty for Notaries in Performing Their Duties Jointly Through Persekutuan Perdata - Nowira, Puti Hanifa; Dewi, Amelia Sri Kusuma; Susilo, Hariyannto (International Journal of Business, Law, and Education, 2025)
This study examines the legal certainty and interpretation of Persekutuan Perdata (Civil Partnership) for Notaries under Undang-Undang Jabatan Notaris. The research aims to clarify the meaning of Persekutuan Perdata as stipulated in the Act and to determine the most suitable business entity form that aligns with the independent nature of the notarial profession, ensuring legal certainty for all parties involved. A normative juridical method, incorporating statutory and conceptual approaches, was applied to analyse the legal characteristics, rights, obligations, and liabilities of each form of non-legal entity business. The results indicate that although the Act designates Persekutuan Perdata as the legal form for Joint Notary Offices, its undefined concept creates legal uncertainty. Based on the analysis of organisational structure, activities, capital, and liability, Maatschap is concluded to reflect best the characteristics and professional independence required of Notaries, compared to Firma or Commanditaire Vennootschap.